Современная школа: состояние тупика или движение вперед (SCIENCE and SOCIETY, 2020)
The article raises the problem of young generation‘s disinterest in reading books. The article describes the actual errors in texbooks on the Russian literature. A suggestion is given about the reasonableness in the choice of literary texts for inclusion in the school curricu- lum.